Bioanalysis Young Investigator: Eugene Ciccimaro. (April 2012) - Ciccimaro, Eugene; Blair, Ian A
Supervisor''s supporting comments Eugene Ciccimaro is one of the most talented graduate students that I have trained. Initially, during his thesis research he developed a novel LC–MS approach for the quantification of phosphorylated proteins. This enabled him to analyze 29 phosphorylated and nonphosphorylated tryptic peptides from focal adhesion kinase. Aspects of this work were presented as posters at the American Society for Mass Spectrometry (ASMS) and Human Proteome Organization (HUPO) meetings. He then developed novel stable isotope dilution methodology, which made possible, for the first time, absolute quantification of phosphorylated proteins. These findings were published in a well-cited paper and the technique was used to monitor the effects of a Src inhibitor in vivo . Since graduating he has been a regular presenter at ASMS and HUPO meetings, and recently co-wrote an insightful review on quantitative biomarker analysis. Eugene was a key member of the team that developed new approaches to serum estrogen quantitation and synaptic protein expression in vivo . He is currently developing groundbreaking new methods for the quantification of proteins and biologically important serum sphingolipids. This latter study will provide technology for studying an underdeveloped and important area of bioanalysis. Therefore, I believe that this talented young scientist is an outstanding candidate for the Bioanalysis Young Investigator Award.